The Role of Forestry in the Indian Economy - Chatterjee, N. (Indian Forester, 1978)
An attempt is made in this paper to empirically evaluate the role played by forest commodities as producer goods in the Indian economy. This role is appraise in terms of their impact on material production employment generation, and the achieyement of self-sufficiency. A formal model, on which the analyses are based is first introduced. The relevent methodological aspects are presented and the resu1ts are discussed. The possible contributions that the Forest Corporations could make are also highlighted, in the light of the appraisals made.